2020
DOI: 10.1016/j.neurobiolaging.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

What electrophysiology tells us about Alzheimer's disease: a window into the synchronization and connectivity of brain neurons

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
163
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(188 citation statements)
references
References 147 publications
(143 reference statements)
5
163
2
Order By: Relevance
“…Moreover, the data presented here suggest that electrophysiological biomarkers can be informative in the differential diagnosis among cognitive function deficits by revealing their neuropsychological etiology. These pieces of evidence, together with the suitability and easiness of the use of EEG in outpatient settings (Cecchi et al, 2015), strongly warrant the use of electrophysiological markers in the AD population (Babiloni et al, 2020).…”
Section: General Conclusionmentioning
confidence: 99%
“…Moreover, the data presented here suggest that electrophysiological biomarkers can be informative in the differential diagnosis among cognitive function deficits by revealing their neuropsychological etiology. These pieces of evidence, together with the suitability and easiness of the use of EEG in outpatient settings (Cecchi et al, 2015), strongly warrant the use of electrophysiological markers in the AD population (Babiloni et al, 2020).…”
Section: General Conclusionmentioning
confidence: 99%
“…In addition to the use of the aforementioned biomarkers, additional tests should be conducted to obtain a complete picture of the status of a potential AD patient. These analyses may involve neurological observation, neuropsychological tests or the use of electroencephalography (EEG) or event-related potential (ERP) indices [ 67 ] as biomarkers of AD [ 68 ]. In this regard and the context of cognitive function, the contribution of gamma oscillations also emerges as a relevant feature to examine in potential patients [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible biomarker for use in AD diagnosis is alteration of oscillatory brain activity. The most widely known oscillatory changes in AD patients are spectral changes, which include slowing of the peak frequency and increase in slow oscillations (8), even in the preclinical phase (9,10). The recent advent of the use of complex network analysis in electroencephalography (EEG) and magnetoencephalography (MEG) studies has revealed abnormal neural oscillations of AD (8,11,12).…”
Section: Introductionmentioning
confidence: 99%